Feasibility randomised controlled trial examining the effects of the Anti-Doping Values in Coach Education (ADVICE) mobile application on doping knowledge and attitudes towards doping among grassroots coaches - Richard Bailey; Adam Robert Nicholls; Lucas R W Fairs; Mar Plata-Andrés; Edward Cope; Daniel Madigan; Katrin Koenen; Iva Glibo; Nikolaos C Theodorou; Jean-Francois Laurent; Gaetan Garcia; Benoit Chanal (BMJ Open Sport & Exercise Medicine)
Objectives Sports coaches are influential in whether athletes dope, but receive very little antidoping education, particularly within entry-level coaching qualifications. We tested the feasibility of an antidoping intervention, delivered via a mobile application, which was designed to increase coaches’ knowledge of doping and to reduce favourable doping attitudes.Methods A two-arm randomised controlled trial, with grassroots coaches who coach young amateur athletes aged between 14 and 18 years of age, was conducted. The Anti-Doping Values in Coach Education (ADVICE) mobile application included modules on fair play, substances, nutritional supplements, rules and leadership. The primary outcome was the change in doping knowledge, 6 weeks after receiving the mobile application. The secondary outcome was changes in doping attitudes.Results Grassroots coaches (n=200; aged between 18 and 71 years, with between 1 and 42 years of coaching experience) from 29 different countries completed baseline assessments, and 85 completed follow-up assessments, and were included in mixed analysis of variance analyses. The intervention increased coaches’ knowledge about doping and also reduced favourable doping attitudes in the experimental arm.Conclusion The ADVICE mobile application is a feasible method for delivering and increasing grassroots coaches’ knowledge of banned substances and the potential side effects of doping. Mobile application-based resources could facilitate a much wider dissemination of antidoping education.